Effects of heat treatment under low moisture conditions on the protein and oil in soybean seeds. (1st March 2019) - Mizutani, Yukiko; Shibata, Masayuki; Yamada, Saeko; Nambu, Yuko; Hirotsuka, Motohiko; Matsumura, Yasuki
Highlights: Heat treatment of soybean seeds only partially denatured the protein. The oil distribution in soybean seeds changed after heat treatment. Lipoxygenase was susceptible to heat denaturation. Microwaves are effective in changing the properties of the soybean components. Abstract: The effects of autoclave and microwave heating on the protein and oil in soybean seeds were investigated under low moisture conditions. The nitrogen solubility index (NSI) decreased on heating. The reduction in the NSI was accompanied by an increase in the size and deformation of the oil bodies in the cellular tissue of soybean seeds. Sodium dodecyl sulfate–polyacrylamide gel electrophoresis analysis revealed that lipoxygenase was susceptible to heat denaturation, but 7S and 11S globulins were only partially denatured. The partial denaturation of the proteins was confirmed by Fourier transform infrared spectroscopy measurements. The ratio of oil to protein peaks increased with increasing heating, suggesting the exudation of oil to the surface or outside of oil bodies. Microwave heating is more efficient in changing the oil distribution in soybean seeds than autoclave heating. On the other hand, the degree of protein denaturation is lower after microwave heating.